PEMBENTUKAN KARAKTER PESERTA DIDIK MELALUI PERGURUAN TAPAK SUCI DI SMA MUHAMMADIYAH KALOSI KECAMATAN ALLA - Haryani Haryani; Andi Kasmawati; Dr. Mustaring, M.Hum (Jurusan Pendidikan Pancasila dan Kewarganegaraan (PPKn), 2019)
Abstract: This study aims, (1) To find out the character values contained in the Tapak Suci College at SMA Muhammadiyah Kalosi (2) To find out the process of forming character values for students through the Tapak Suci College at SMA Muhammadiyah Kalosi (3) To find out the barriers to the formation of character values for students through the Tapak Suci College at SMA Muhammadiyah Kalosi. To achieve this goal, the researchers used data collection techniques through documentation, observation and interviews. The data that has been obtained from the research results are processed using qualitative analysis to determine the character formation of students through the Tapak Suci College at SMA Muhammadiyah Kalosi. The results showed that: (1) the character values contained in the Tapak Suci College at SMA Muhammadiyah Kalosi were the values of religious character, honesty, discipline, hard work, respect for achievement, responsibility, independence, humility, patience, accuracy, leadership, agility. , cooperation and love of peace. (2) the process of forming character values in the Tapak Suci College at SMA Muhammadiyah Kalosi can be formed through materials and methods in the training process. (3) barriers to the formation of character values in the Tapak Suci College at SMA Muhammadiyah are the environment where students live, short training time, inadequate training equipment, lack of joint training for cadres and lack of number of trainers. Based on this, it can be said that there are several processes of forming character values that are less than optimal.Keywords: Formation, character, students